Telephone courtesy & customer service - Finch, Lloyd C. (Crisp Pub. Menlo ParkUS, 1990)
Reviews the basics for providing quality customer service. Examines 18 telephone techniques including: addressing the caller; answering the telephone; managing different caller behaviours e.g. talkativeness, and anger. Explains customer wants and needs, and emphasizes the importance of positive attitude. Provides guidelines for managing customer perceptions.